Identification of phenolic compounds in red wine extract samples and zebrafish embryos by HPLC-ESI-LTQ-Orbitrap-MS. (15th August 2015) - Vallverdú-Queralt, Anna; Boix, Nuria; Piqué, Ester; Gómez-Catalan, Jesús; Medina-Remon, Alexander; Sasot, Gemma; Mercader-Martí, Mercè; Llobet, Juan M.; Lamuela-Raventos, Rosa M.
Highlights: Polyphenol compounds have been identified in red wine extracts. Polyphenols in zebra fish (ZF) embryos, exposed to the red wine extract, were determined. First comprehensive identification of phenolic compounds in ZF using LTQ-Orbitrap. The metabolic capacity of ZF embryos was observed. Abstract: The zebrafish embryo is a highly interesting biological model with applications in different scientific fields, such as biomedicine, pharmacology and toxicology. In this study, we used liquid chromatography/electrospray ionisation-linear ion trap quadrupole-Orbitrap-mass spectrometry (HPLC/ESI-LTQ-Orbitrap-MS) to identify the polyphenol compounds in a red wine extract and zebrafish embryos. Phenolic compounds and anthocyanin metabolites were determined in zebrafish embryos previously exposed to the red wine extract. Compounds were identified by injection in a high-resolution system (LTQ-Orbitrap) using accurate mass measurements in MS, MS 2 and MS 3 modes. To our knowledge, this research constitutes the first comprehensive identification of phenolic compounds in zebrafish by HPLC coupled to high-resolution mass spectrometry.